Performance Analysis Of Secured Fiber Optics Communication Technologies In Computer Networking And Security Challenges - Parthasarathy, Rajamohan; Ayyappan, Preethy; Loong, Seow Soon; Rajamanickam, Leelavathi; Kumar, A. Senthil (International Journal of Psychosocial Rehabilitation, 2020)
Fiber Optics Communication is also one of the major branch which is widely used in current communication world. Due to several advantages of fiber optics communication over different conventional wired communication method it is having higher priority. Though fiber optic transmits large amount of data quickly over long distance, it is vulnerable to various security attacks. The fiber optic cable can be easily tapped. Fundamental improvements can be achieved for the entire network by increasing the optical network’s performance in terms of channel capacity, data rate, and processing speed. Furthermore, the security of the optical network has an impact on the security of the entire communication system. Optical network security can be effectively protected by fiber-based methods, including all optical signal processing, optical key distribution, optical steganography, and optical chaos-based communication. Fiber-based devices do not radiate an electromagnetic signature and are immune to electromagnetic interference. To provide end to end secure fiber optic communication, a special encryption algorithm based on Advanced Encryption Standard (AES) is employed. The proposed encryption algorithm is simulated and the performance is analyzed. In this paper we are mostly dealing with the basics of fiber optics working principle, priority over other conventional communication system and role of fiber optics communication in computer networking and its vulnerabilities.